The Prophet Balaam in a 6th Century Aramaic Inscription - Hoftijzer, Jacob (The Biblical archaeologist, 1976)
In Numbers 22-24, Balaam, a non-Israelite prophet, is ordered by the King of Moab in Transjordania to curse the invading Israelites. Instead, through God's intervention, Balaam blesses them. In 1967, at Tell Deir- ˓Alla in Jordan, curses of Balaam were found inscribed on a stele.